Lebrikizumab improves head/neck/face dermatitis and erythema and does not increase treatment-emergent adverse events of head/neck/face erythema in patients with moderate-to-severe atopic dermatitis - Jenny E. Murase; Kilian Eyerich; Raj Chovatiya; H. Chih-ho Hong; Christine Bangert; Lindsay Strowd; Mette Deleuran; Amber Reck Atwater; Maria Jose Rueda; Hany Elmaraghy; Maria Lucia Buziqui Piruzeli; Ignasi Pau-Charles; et al. (Journal of Dermatological Treatment)
Purpose of the study Head, neck (HN), and face involvement in atopic dermatitis (AD) poses a major psychological burden and can be challenging to effectively treat. New appearance of HN dermatitis has been reported with biologics used to treat AD. Lebrikizumab (LEBRI), a monoclonal targeting IL-13, is approved for AD treatment in the US, Europe and Asia. We evaluated HN dermatitis improvement using the HN Eczema Area and Severity Index (EASI) and a facial dermatitis questionnaire, along with safety evaluations focusing on HN and facial erythema.Materials and methods Efficacy analyses were performed on placebo (PBO) controlled modified intention-to-treat (mITT) populations from the 16-week induction periods of ADvocate1 and ADvocate2 (pooled) and ADhere studies. Treatment-emergent adverse events (TEAEs) of HN and facial erythema were summarized from eight Phase 2 and 3 clinical trials.Results LEBRI resulted in significantly greater improvements than PBO in EASI HN subscore as early as Week 2 (ADvocate 1&2), with 68.1% improvement at Week 16.Conclusions LEBRI improved EASI HN subscore and HN EASI clinical signs of erythema and facial dermatitis at Week 16. During the PBO-controlled period, an increased reporting of HN and facial erythema as TEAE was not observed in the LEBRI group and HN and facial TEAEs reporting did not increase with longer exposure.